INJURY OF SUBCLAVIAN ARTERY IN SEVERE TRAUMA OF THE SHOULDER GIRDLE AND CHEST - I. M. Samokhvalov; V. A. Reva; A. A. Pronchenko; A. N. Petrov (Вестник хирургии имени И.И. Грекова)
The authors consider one of possible variants of surgical treatment of shoulder girdle trauma, which is accompanied by an injury of the main artery. It is based on the application of the principle of staged surgical treatment (damage control orthopedic). The well-timed sufficient diagnostics and treatment of bone-arterial trauma, coordinated work of several surgical teams, the appropriate postoperative management of patients with the using of postponed high-technology intervention allowed obtaining an optimal functional result for extremely severe multitrauma of the chest and limb.